2014
DOI: 10.1590/s1517-83822014000100035
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis in southern Rio Grande do Sul: a retrospective study of histopathologically diagnosed cases

Abstract: Paracoccidioidomycosis (PCM) is a systemic mycosis caused by the fungus Paracoccidioides brasiliensis and is endemic to Brazil. The aim of this study was to perform a retrospective analysis of the PCM cases in the countryside south of Rio Grande do Sul, Brazil. The files from four histopathology laboratories located in the city of Pelotas were obtained, and all of the epidemiological and clinical data from the PCM diagnosed cases were collected for analysis. A total of 123 PCM cases diagnosed between 1966 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 15 publications
1
26
0
3
Order By: Relevance
“…All the cases in question were diagnosed by histopathological examination of biopsied specimens of oral lesions. The incisional biopsy was the most used technique (85.45% of cases) for diagnosis, and shown to be effective in the diagnosis of oral lesions as demonstrated in other studies . Some differential diagnosis should be included to such injuries, especially squamous cell carcinoma, tuberculosis, sarcoidosis and Wegener's granulomatosis …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…All the cases in question were diagnosed by histopathological examination of biopsied specimens of oral lesions. The incisional biopsy was the most used technique (85.45% of cases) for diagnosis, and shown to be effective in the diagnosis of oral lesions as demonstrated in other studies . Some differential diagnosis should be included to such injuries, especially squamous cell carcinoma, tuberculosis, sarcoidosis and Wegener's granulomatosis …”
Section: Discussionmentioning
confidence: 95%
“…reported that 45.5% of 422 patients were rural workers, Bicalho et al . found this association in 53% of patients and Souza et al . found that 65.2% lived in rural areas or working with agriculture.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…About 30% to 50% of the chronic PCM patients exhibit oral manifestations, characterised by erythematous granular ulcers with haemorrhagic dots that is called moriform stomatitis involving mainly hard and soft palate, buccal, labial and gingival mucosa, or severe periodontal bone loss . Oral PCM manifestations favour the recognition of the disease and make possible the diagnosis through incisional biopsy …”
Section: Introductionmentioning
confidence: 99%
“…The majority of the PCM cases (around 80%) are reported in Brazil (7,8), which is the first one cause of death among systemic mycoses disease in the country (1,9). Different distribution in endemic areas and the difficult to notify the Original Article Paracoccidioidomycosis: level of pulmonary sequelae in high resolution computed tomography images from patients of two endemic regions of Brazil disease are facts, which contributes negatively to establish incidence and prevalence of PCM (10,11).…”
Section: Introductionmentioning
confidence: 99%